2021
DOI: 10.3389/fnut.2021.552049
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fibers (Gum Arabic) Supplementation Modulates Hepatic and Renal Profile Among Rheumatoid Arthritis Patients, Phase II Trial

Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune disease that mainly affects the synovial joints with systemic manifestations. RA has a major impact on liver and kidney functions as part of the disease pathogenesis or as a sequel of disease medications or, mostly, both of them. The kidney and liver involvement increases the RA morbidity and mortality. Nowadays, dietary interventions are proposed as potential modifiers for disease severity. Gum Arabic (GA) is acacia senegal exudates; it is soluble fiber w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…higher than that of NAC administration. This finding was following a recent finding conducted on a patient with rheumatoid arthritis suffering from renal affection to find that AG was able to decrease levels of urea in those patients 22 .…”
Section: Discussionsupporting
confidence: 67%
“…higher than that of NAC administration. This finding was following a recent finding conducted on a patient with rheumatoid arthritis suffering from renal affection to find that AG was able to decrease levels of urea in those patients 22 .…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the same group demonstrated that GA significantly reduced liver enzymes and urea levels, while concurrently increasing serum albumin levels. These findings suggest the potential for GA to modulate the hepatic and renal profiles of patients with RA (Kamal et al, 2021). While a substantial portion of GA research has traditionally focused on its GI health benefits, there is an increasing interest in investigating its potential advantages for managing other inflammatory conditions, including RA, soon.…”
Section: Gum Acacia On Inflammation and Inflammatory Diseasesmentioning
confidence: 97%
“…51 Dietary fiber supplementations have been reported to improve the residual renal and peritoneal function. 52 In addition, the biologic methylation of As promotes its urine elimination, and microbiota-driven therapies have been reported to significantly increase the methylation of As. 53,54 In the present study, a significant decrease in albumin loss by residual renal and peritoneum was observed with ITFs, accompanied by an increase in the clearance rate of As through the urine and dialysate, indicating the negative regulation of As clearance by dialysis and urine on the plasma As level with ITF intervention.…”
Section: Papermentioning
confidence: 99%